2014
DOI: 10.1111/jir.12142
|View full text |Cite
|
Sign up to set email alerts
|

Development of physical fitness in children with intellectual disabilities

Abstract: Despite statistically significant development of physical fitness in children with ID, their physical fitness levels should be stimulated. This should start already in young children (<8 years) and the children with the most severe cognitive impairments need special attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 33 publications
3
51
2
1
Order By: Relevance
“…36 In a recent study, children and youth with intellectual disabilities were found to have poor physical fitness compared with typically developing children. 37 Niederer et al found that higher baseline cardiorespiratory fitness and motor skills corresponded to better spatial working memory or attention in preschool children. 38 Likewise, Krombholz noted positively significant correlations between measures of physical growth and physical performance and between motor and cognitive performance, physical fitness, body coordination, and manual dexterity, in preschool children, which improved with age group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 In a recent study, children and youth with intellectual disabilities were found to have poor physical fitness compared with typically developing children. 37 Niederer et al found that higher baseline cardiorespiratory fitness and motor skills corresponded to better spatial working memory or attention in preschool children. 38 Likewise, Krombholz noted positively significant correlations between measures of physical growth and physical performance and between motor and cognitive performance, physical fitness, body coordination, and manual dexterity, in preschool children, which improved with age group.…”
Section: Discussionmentioning
confidence: 99%
“…Wassenberg et al noted the parallel development of specific cognitive and motor performance in children during normal or delayed development: specific brain structures, such as the basal ganglia or frontal cortex, and dopamine transmission are involved in both cognitive and motor performance . In a recent study, children and youth with intellectual disabilities were found to have poor physical fitness compared with typically developing children . Niederer et al found that higher baseline cardiorespiratory fitness and motor skills corresponded to better spatial working memory or attention in preschool children .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies of young people and adults with ID have consistently shown negative differences in general fitness and specifically, cardiovascular endurance, muscular strength, endurance, and range of motion (Hartman, Smith, Westendorp, & Visscher, 2014;Salaun, & Berthouze-Aranda, 2012;Cuesta-Vargas, Paz-Lourido, & Rodriguez, 2011;Zhang, Piwowar, & Reilly, 2009;Faison-Hodge & Porretta, 2004). This has been related to general levels of physical activity being lower in this population, however when considering the potential to attain high standards of physical fitness a more mixed picture emerges.…”
Section: Physiological and Fitness Factorsmentioning
confidence: 99%
“…They are known to present a greater risk for a variety of health concerns compared with the general population . In addition, emerging findings also suggest that individuals with intellectual disabilities may experience greater levels of difficulties with motor development and fundamental movement skills and be characterized by lower levels of physical fitness than typically developing individuals. More specifically, studies show that young people with intellectual disabilities tend to be characterized by a significantly lower balance or postural control than typically developing peers …”
mentioning
confidence: 99%